Sensed fittingness between act and consequence: The last acts of Esther in the book of Esther and Grace in the film Dogville - Snyman, Gerrie 19XX- (HTS teologiese studies, 2013)
The book of Esther employs a wisdom theme to develop the plot and its denouement. The particular illustration of wisdom is that of role reversal. Haman, the second in command, gets kicked out and the leaders of those he sought to lock out filled his position. However, the role reversal becomes more than a mere change in status. As Grace needed to step into her gangster father’s shoes in the film Dogville in order to achieve justice, so Esther had to step into Persian shoes to achieve justice. The execution of justice is an untidy and messy affair. The question this article puts on the table is whether Esther acts with justice in her quest for retribution. In answering this question, the article firstly inquires into the narrative rationality of the story and the denouement of the plot. Related to the book of Esther’s narrative rationality, the article examines the question of wisdom from a narrator’s and character’s perspective. Lastly, it will then put the issue of justice on the table with the help of the film Dogville in order to see whether there is a link between wisdom and justice.